Non-mosaic partial duplication 12p in a patient with dysmorphic characteristics and developmental delay - Oliveira, Jakeline Santos [UNESP] (2020)
Duplication of the short arm of chromosome 12 is a rare chromosomal abnormality that may arise de novo or result from malsegregation of a balanced parental translocation. This study comprises the clinical description, cytogenetic and cytogenomic analyses and genotype-phenotype correlation in a patient with facial dysmorphism, developmental delay and intellectual impairment caused by non-mosaic partial duplication and a paracentric inversion 12p. The pa-tient’s GTG-banded karyotype was 46,XX,invdup(12)(pter → p13.32